2020
DOI: 10.1186/s12958-020-00587-y
|View full text |Cite
|
Sign up to set email alerts
|

Performing ICSI within 4 hours after denudation optimizes clinical outcomes in ICSI cycles

Abstract: Background: The study aimed to investigate whether and how general and partial time intervals between processes, from human chorionic gonadotrophin (HCG) trigger to intracytoplasmic sperm injection (ICSI), affected the laboratory and reproductive outcomes in ICSI cycles. Methods: This was a retrospective data analysis of 3602 women who underwent ICSI treatment cycles using partner or donor sperms, performed at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
4
13
0
Order By: Relevance
“…Seventeen studies reported data on the effect of OPU-DN on fertilisation rate. Among them, 11 reported no significant effect of OPU-DN time on fertilisation rate, which was similar to the conclusion of a recent study, suggesting no correlation between OPU-DN time and fertilisation rate [ 33 ]. However, six studies considered that OPU-DN time did affect fertilisation rate, and five of these believed that the fertilisation rate would increase with the extension of OPU-DN time [ 2 , 4 , 15 , 17 , 23 ].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Seventeen studies reported data on the effect of OPU-DN on fertilisation rate. Among them, 11 reported no significant effect of OPU-DN time on fertilisation rate, which was similar to the conclusion of a recent study, suggesting no correlation between OPU-DN time and fertilisation rate [ 33 ]. However, six studies considered that OPU-DN time did affect fertilisation rate, and five of these believed that the fertilisation rate would increase with the extension of OPU-DN time [ 2 , 4 , 15 , 17 , 23 ].…”
Section: Resultssupporting
confidence: 84%
“…Another study showed that the fertilisation rate was stable within 6 h after degranulation, and the stability decreased remarkably after 6 h [ 3 ], while two others suggested that prolonging the time of DN-ICSI could increase the fertilisation rate [ 4 , 20 ]. However, one recent study that grouped subjects according to DN-ICSI time found that, although the fertilisation rate gradually increased with incubation times up to 5 h, it decreased considerably after 5 h [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations